Talent Management-Based Training Planning to Produce High-Performing Human Resources - Yusuf Arifin (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study focuses on the process of talent management-based training planning, which is expected to generate high-performing human resources. The research method used is qualitative with a descriptive exploratory approach, with the research output being the stages of talent management-based training planning. The objective of this research is to design the stages of talent management-based training planning along with its supporting instruments, in order to produce high-performing human resources. The implementation of talent management in human resources training is one of the strategies that companies can use to obtain human resources with excellent performance quality, as well as to assess, train, and optimize the human resources owned by the company, where talent management can address retention or employees' desire to leave the organization. The impact of talent management implementation in the implementation of human resources training that adopts the DISC personality concept (Dominance, Influence, Steadiness, and Compliance) is expected to benefit both the company and the relevant employees, as follows: (1) Improving the business value of the company to shareholders; (2) Increasing customer satisfaction; (3) Enhancing the quality, productivity, and capabilities of human resources; (4) Boosting employee motivation and commitment to high performance; (5) Facilitating career development and mapping for employees; (7) Enhancing employees' contribution of knowledge to company objectives.